Improving the treatment paradigm for non-Hodgkin’s lymphoma with bortezomib (Hematology Meeting Reports, 2009)
Targeting of the ubiquitin proteasome pathway has proven to be a valid and efficacious approach for the treatment of several hematologic malignancies, especially multiple myeloma and select non-Hodgkin's lymphoma (NHL) sub-types. To date, several ongoing phase II clinical studies have independently and clearly documented the activity of bortezomib in select sub-types of NHL. What has emerged from the available data is that there may be significant differences among the different sub-types of lymphoma with regard to their sensitivity of proteasome inhibition and the kinetics of the response.